2018
DOI: 10.1097/mao.0000000000001638
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mitoquinone for Protecting Against Amikacin-Induced Ototoxicity in Guinea Pigs

Abstract: Oral or subcutaneous MitoQ provided limited protection against amikacin-induced hearing loss and cochlear damage in guinea pigs. Other strategies for attenuating aminoglycoside-induced ototoxicity should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Moreover, two previous in vivo studies found protective effects of MitoQ in the inner ear. Using gentamicin- or amikacin-treated guinea pigs, it was shown that the administration of MitoQ attenuated aminoglycoside-induced ototoxicity, leading to cochlear damage and hypoacusia [44] , [45] . Although the protective effect of MitoQ against ototoxicity was determined in previous studies, an important significance of this study is the suggestion of the possibility to reverse genetic hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two previous in vivo studies found protective effects of MitoQ in the inner ear. Using gentamicin- or amikacin-treated guinea pigs, it was shown that the administration of MitoQ attenuated aminoglycoside-induced ototoxicity, leading to cochlear damage and hypoacusia [44] , [45] . Although the protective effect of MitoQ against ototoxicity was determined in previous studies, an important significance of this study is the suggestion of the possibility to reverse genetic hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…We screened all 20 identified records and removed all studies that were not relevant to the subject matter. The remaining 8 records were summarized in this section [9,10,11,12,13,14,15,16]. Among the mitochondria-targeted antioxidants, MitoQ and SkQR1 have been used for studying the treatment of SNHL (Table 1).…”
Section: Mitochondria-targeted Antioxidants For Treatment Of Hearimentioning
confidence: 99%
“…There have been several reports using MitoQ and SkQR1 to demonstrate the protective effect of mitochondria-targeted antioxidants against ototoxicity in animal models and/or mouse auditory cell lines [9,10,11,12,13,14,15,16]. Oral MitoQ treatment reduced gentamicin-induced cochlear damage and hearing loss in guinea pigs [15].…”
Section: Mitochondria-targeted Antioxidants For Treatment Of Hearimentioning
confidence: 99%
See 2 more Smart Citations